2014
DOI: 10.1038/jp.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal iron status is impaired by maternal obesity and excessive weight gain during pregnancy

Abstract: Objective Maternal iron needs increase 6-fold during pregnancy, but obesity interferes with iron absorption. We hypothesized that maternal obesity impairs fetal iron status. Study Design 316 newborns with risk factors for infantile iron deficiency anemia (IDA) were studied to examine obesity during pregnancy and neonatal iron status. Erythrocyte iron was assessed by cord blood hemoglobin (Hb), zinc protoporphyrin/heme (ZnPP/H) and reticulocyte-ZnPP/H and storage iron by serum ferritin. Results Women with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 39 publications
(78 reference statements)
7
70
2
1
Order By: Relevance
“…Currently, known risks for developing iron deficiency as an infant were tallied: maternal obesity (BMI ≥30 kg/m 2 ), maternal diabetes, minority status, Medicaid insurance, and fetal growth disturbance (small or large for gestational age). 13,25 Subjects were selected after electronic medical record evaluation for inclusion and exclusion criteria. All subject data were de-identified.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, known risks for developing iron deficiency as an infant were tallied: maternal obesity (BMI ≥30 kg/m 2 ), maternal diabetes, minority status, Medicaid insurance, and fetal growth disturbance (small or large for gestational age). 13,25 Subjects were selected after electronic medical record evaluation for inclusion and exclusion criteria. All subject data were de-identified.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 An additional study found that lower umbilical tissue iron content was linked to childhood wheezing, 19 but did not measure immune indices at birth. We previously found poorer umbilical cord blood iron status in the presence of maternal obesity or with GWG exceeding 18 kg 13 and also demonstrated that either poor umbilical cord iron status or GWG exceeding 18 kg predicted the development of eosinophilia during the first year of life. 20 Eosinophilia is used to predict the development of allergic asthma.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Decreased placental expression of ferritin may negatively impact the rate of iron uptake from the maternal circulation and transfer to the fetal circulation. Human studies have shown evidence of impaired iron status in newborns of obese women (Phillips et al 2014) and in infants born to diabetic mothers (Siddappa et al 2004). Iron deficiency is known to be associated with impaired brain development (Lozoff et al 1991).…”
Section: Maternal Obesity and Offspring Neurodevelopmentmentioning
confidence: 99%
“…Niewłaściwy stan odżywienia organizmu w ciąży powoduje niedorozwój łożyska (mniejszy jego rozmiar i utrudniony przepływ krwi), co z kolei upośle-dza dowóz składników odżywczych do płodu i rzutuje na krótko-i długoterminowy rozwój neurologiczny i chorobowość dziecka [50]. Ponadto nadmierna masa ciała przed ciążą oraz duży jej przyrost w ciąży jest niezależnym czynnikiem ryzyka niedoborów żelaza (im wyższe BMI, tym mniejsze stężenia żelaza i ferrytyny) [51]. Żelazo jest waż-nym mikroelementem dla rozwoju układu nerwowego płodu i mielinizacji nerwów.…”
Section: Nieadekwatny Stan Odżywienia Na Skutek Złych Nawyków żYwieniunclassified